SIMBOL BAHASA RUPA PADA DINDING DALAM OMO SEBUA DI BAWOMATALUO NIAS SELATAN - ARIESA PANDANWANGI; KRISMANTO KUSBIANTORO (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2017)
Based on the geographical distribution of Nias, it is divided into 4 regions: North Nias, South Nias, East Nias, and West Nias. The focus areas of this research are traditional houses in South Nias, one of which is Omo Sebua (a noble house) in Bawomataluo village. The object of this study was chosen because the traditional house Omo Sebua is rich in traditional Nias decorative symbols on the parts of his house.The purpose of this research is to know the meaning of the symbol on the inside wall of Omo Sebua. This research using qualitative descriptive method with the approach of Visual language to read the symbol. The result of this research reveals that the special Visual language of Omo Sebua tells about the social status and daily life of the Nias people, namely the noble symbol. The symbol is inspired from important events at that time. The symbol also implies that anyone who visits should bow to homeowners.Â Keywords: Nias; Omo Sebua; symbols; visual Language